2022
DOI: 10.1017/s1368980022000246
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of funding sources and conflicts of interest in evidence underpinning vitamin D and calcium recommendations in bone health guidelines

Abstract: Objective: The present study aims to examine the relationship between study funding sources, author conflicts of interest and conclusions in studies supporting vitamin D and calcium intake cited in bone health guideline recommendations. Design: Cross-sectional Setting: 47 global bone health guidelines with vitamin D and/or calcium recommendations for adults aged 40 years and above Participants: The evidence cited to support the recommendations was extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous studies in other fields have also found an absence of COI disclosures, as well as reports of “no disclosures” by authors who had financial relationships with industries, characterizing omission ( 56 ). A recent study that analyzed the evidence supporting global guidelines for vitamin D and calcium recommendations in bone health showed that COI disclosure was low, and studies with absent or unclear COI disclosures were more likely to come to conclusions favorable to vitamin D and/or calcium intake than those with disclosures ( 57 ). In our review we found a lack of clear statements regarding the origins of funding, the sponsor's role in the study as well as a lack of bias and limitations in reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in other fields have also found an absence of COI disclosures, as well as reports of “no disclosures” by authors who had financial relationships with industries, characterizing omission ( 56 ). A recent study that analyzed the evidence supporting global guidelines for vitamin D and calcium recommendations in bone health showed that COI disclosure was low, and studies with absent or unclear COI disclosures were more likely to come to conclusions favorable to vitamin D and/or calcium intake than those with disclosures ( 57 ). In our review we found a lack of clear statements regarding the origins of funding, the sponsor's role in the study as well as a lack of bias and limitations in reporting.…”
Section: Discussionmentioning
confidence: 99%